Growing older with post-polio syndrome: Social and quality-of-life implications. (August 2018) - Duncan, Andrea; Batliwalla, Zinnia
Objectives: To understand the quality-of-life implications for post-polio syndrome survivors. Methods: For this qualitative study, a focus group methodology, with a case study design, was used. The data were analyzed for themes using a social ecological conceptual framework. Results: Three focus groups were conducted with a total of 24 participants (N = 24). Participants defined quality of life as being able to engage in meaningful activities of daily living. Participants shared experiences of adapting to declining physical health and embracing new activities of daily living. They expressed hope and shared stories that demonstrated resiliency. Conclusion: The literature states that individuals aging with post-polio syndrome express concern that health providers often know little about their disability condition. The participants in this study reflected this experience by sharing feelings of misunderstanding from the medical community and expressing a desire to have more dynamic education for health providers.